How Wage Compression Affects Job Turnover - Fredrik Heyman (Research Institute of Industrial Economics (IFN), 2008)
I use Swedish establishment-level panel data to test Bertola and Rogersons (1997) hypothesis of a positive relation between the degree of wage compression and job reallocation. Results indicate that the effect of wage compression on job turnover is positive and significant in the manufacturing sector. The wage compression effect is stronger on job destruction than on job creation, consistent with downward wage rigidity. Further results include a strong positive relationship between the fraction of temporary employees and job turnover and a negative relationship between the amount of working-time flexibility and job reallocation.
Keywords: J21; J31; J63; 330; Job Creation and Job Destruction; Wage Dispersion; Temporary Employment Contracts; Panel Data; Lohnrigidität; Lohnstruktur; Beschäftigungseffekt; Arbeitsmarkt; Zeitreihenanalyse; Schweden